2018
DOI: 10.1097/id.0000000000000731
|View full text |Cite
|
Sign up to set email alerts
|

Successful Use of Leukocyte Platelet-Rich Fibrin in the Healing of Sinus Membrane Perforation

Abstract: The use of L-PRF associated with collagen membrane was efficient for the sealing of the sinus membrane perforation and enabled bone formation for subsequent implant installation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
3
0
3
Order By: Relevance
“…Previous studies demonstrated the repair of such a defect with the sole application of a collagen sponge [ 25 ] or PRF [ 19 , 27 ]. Additionally, the combined use of the PRF and collagen membrane is shown to be efficient for sealing large sinus membrane perforation and enabling bone formation for subsequent implant placement [ 42 ]. A report of case series compared the bone height at sites with perforated Schneiderian membrane repaired using the PRF/collagen combination to others with intact membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated the repair of such a defect with the sole application of a collagen sponge [ 25 ] or PRF [ 19 , 27 ]. Additionally, the combined use of the PRF and collagen membrane is shown to be efficient for sealing large sinus membrane perforation and enabling bone formation for subsequent implant placement [ 42 ]. A report of case series compared the bone height at sites with perforated Schneiderian membrane repaired using the PRF/collagen combination to others with intact membrane.…”
Section: Discussionmentioning
confidence: 99%
“…A utilização do L-PRF no reparo das perfurações da membrana sinusal tem sido reportada na literatura como uma opção de tratamento. Possui propriedades de adesividade natural e alta resistência devido a sua rede de fibrina, o que pode evitar que as partículas do enxerto migrem para dentro do seio maxilar (Öncü & Kaymaz, 2017;Dos Santos Pinto, et al, 2018;De Almeida Malzoni, et al, 2021). Pela sua adesividade, permite que se unam podendo reparar perfurações maiores e também a possibilidade de sutura-las devida a sua alta resistência (Wallace & Froum, 2019).…”
Section: Discussionunclassified
“…Esta característica le da una resistencia igualmente equilibrada en toda la estructura (21), lo que permite usar el PRF como membrana de protección o como una pared para soportar otros materiales, es decir no tiene ninguna limitación en cuanto a la ubicación o a la forma en que se coloque. Se puede usar en cirugías de perforaciones sinusales como una membrana (24), para colocarla como pared de protección en lesiones óseas para contener algún biomaterial, como por ejemplo en el manejo de fenestraciones (25), también se puede utilizar colocando otro biomaterial entre dos membranas (26).…”
Section: Discussionunclassified